Effect Of Young Age in Murder Felony (Comparative Study Between Islamic Jurisprudence and Indonesian Law) - Islamul Haq; M. Ali Rusdi Bedong; Abdul Syatar (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
This research was a comparative study on the effect of young age in the crime of murder between Islamic jurisprudence and Indonesian law. The presence of children around us needs attention, especially with regard to their behavior, which is out of control. the phenomenon of their deviation is one of the negative social phenomenon which required protection, guidance and education. According to previous studies, children who deviated and were not controlled would become a criminal when he reaches adulthood. Nowadays, the children's delinquency is widely spread, they are involved in committing crimes such as drugs, theft, fighting, and increased to murder. This research will focus on the murder committed by under age children, because murder is a very dangerous crime to the indivdual life and is one of the law violation againts the five principles of shariah (daruriyat al khamsah).